Analisis Perilaku Konsumen Muslim Dalam Belanja Melalui Shopee Saat Pandemi Covid-19 Berdasarkan Perspektif Islam - Putrisma Iffa Rosada; Mohammad Syifa Amin Widigdo (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to investigate the behavior of Muslim consumers in shopping through Shopee before the Covid-19 pandemi, behavioral changes during and after the Covid-19 pandemic analyzed from Islamic perspective. The method in this study used a qualitative research method using the type of field research. This study shows that before the Covid-19 pandemi, the behavior of Muslim consumers of IRPSM and IRPSI was following the principles, ethics, and limits of Islamic consumption. They shop according to their needs and shop in sufficient quantities. However, during the Covid-19 pandemi, Muslim consumers experience a behavioural change. These changes can be seen in the emergence of new motives for choosing online shopping at Shopee which results in shopping not only based on needs but also because of desire. This has increased the amount of consumer spending that is considered not following Islamic principles, ethics, and consumption limits.